Peningkatan Kualitas Kompetensi Pedagogik Guru SDN Teluk Tiram 2 Banjarmasin dalam Mengembangkan Perangkat Pembelajaran - Norjenah (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
One role of teacher in learning, that is as learning planning, each teacher education, i fon a unit to develop syllabus and lesson plans to complete and systematic excellencent learning effevtive. education excellent held effectively will led on improving the quality of processes and students study results. but there were various good a deficiency to the syllabus prior preparation and lesson plans. one of alternatives that used to increase the qualtiy of teachers plan pedagogik lesson plans anda syllabus with the specified criteria, to apply workshop of kkg mini. Teachers to raise their level of understanding SDN Teluk Tiram 2 in preparing and developing syllabus and lesson plans, maket he most of teachers SDN Teluk Tiram 2 in the prepation of the development of the syllabus and lesson plans, you make a teacher to be more professional in learning activities for preparation. Methods used in research the act of this school reduce reseach the act of class. Step this study the planned two cycles. Workshop before held the kkg mini category only get scores and some did not understand, after the workshop activities set up the kkg mini category get value very good all teachers are already proficient in preparing and developing a syllabus and lesson plans. By looking at the outcome I, cycle improvements in the act of but are still required act of repairing the II through the cycle the second direction from the link to give information and guidance on what felt it was still hard, I cycle especially in determining, exploration elaboration and confirming the components core learning activities.